Mycorrhizae helper bacteria for managing the mycorrhizal soil infectivity - Nasslahsen, Bouchra; Prin, Yves; Ferhout, Hicham; Smouni, Abdelaziz; Duponnois, Robin (Frontiers in Soil Science, 2022)
Arbuscular mycorrhizal fungi are major components of soil microbiota and mainly interact with other microorganisms in the rhizosphere. Mycorrhiza establishment impacts the plant physiology and some nutritional and physical properties of the rhizospheric soil. These effects alter the development of the root or mycorrhizas resulting from the activity of soil microorganisms. The rhizosphere of mycorrhizal plants (mycorrhizosphere), is inhabited by large microbial activities responsible for several key ecosystem processes. This review is focused on the microbial interactions between mycorrhizal fungi and components of rhizosphere microbiota and highlight the agronomic potentialities of the Mycorrhiza Helper Bacteria on mycorrhiza formation. The main conclusion is that this MHB effect in the rhizosphere of mycorrhizal plants, enhance plant fitness and soil quality and are of great interest to ensure sustainable agricultural development and ecosystem functioning.